Functional adequacy in L2 writing: Towards a new rating scale. (July 2017) - Kuiken, Folkert; Vedder, Ineke
The importance of functional adequacy as an essential component of L2 proficiency has been observed by several authors (Pallotti, 2009; De Jong, Steinel, Florijn, Schoonen, & Hulstijn, 2012a, b). The rationale underlying the present study is that the assessment of writing proficiency in L2 is not fully possible without taking into account the functional dimension of L2 production. In the paper a rating scale for functional adequacy is proposed, containing four dimensions: (1) content, (2) task requirements, (3) comprehensibility, and (4) coherence and cohesion. The scale is an adaptation of the global rating scale of functional adequacy, which in an earlier study was carried out with expert raters (Kuiken, Vedder, & Gilabert, 2010; Kuiken & Vedder, 2014). The new rating scale for functional adequacy was tested out by a group of non-expert raters, who assessed the functional adequacy of a corpus of argumentative texts written by native and non-native writers of Dutch and Italian. The results showed that functional adequacy in L2 writing can be reliably measured by a rating scale comprising four different subscales.